Uncharted territory: endometeriosis explored in the left canal of Nuck - Gupta, Rekha; Sachar, Chandrika; Aggarwal, Phiza (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
In this captivating exploration, we unravel a perplexing case of endometriosis taking root within the enigmatic left canal of Nuck. A 33-year-old woman with a tenacious groin mass, manifesting occasional discomfort during menstruation, led us down a diagnostic rabbit hole. Through ultrasound and MRI revelations, a mass emerged, stretching through the left inguinal canal into the pubic domain. The subsequent cytological analysis solidified the diagnosis. While endometriosis, characterized by extrinsic endometrial tissue, typically confines its grip to the pelvic arena, this singular case defies convention. The canal of Nuck, a developmental vestige, reveals itself as a potential portal for endometrial cells under enigmatic conditions. Amid diagnostic intricacies, ultrasound and MRI step forth as guiding imaging tools. In a medical landscape rife with the known, this expedition into the uncharted expands our understanding and beckons us to probe further into the remarkable intricacies of Nuck's canal endometriosis.